Pulmonary infarction with phlegmasia cerulea dolens: a sequelae of deep vein thrombosis - Bajpai, Rashmi Gupta (International Journal of Research in Medical Sciences, 2025)
Deep vein thrombosis (DVT) can lead to severe complications such as pulmonary embolism and phlegmasia cerulea dolens (PCD), both of which are life-threatening conditions. The coexistence of infected pulmonary infarction and PCD is exceptionally rare, demanding timely diagnosis and multidisciplinary management. A 70-year-old male with diabetes and sepsis presented with fever, limb pain, and swelling. Investigations included Doppler ultrasound, computed tomography (CT) angiography, and positron emission tomography (PET) - CT scans, confirming DVT, pulmonary embolism, and Aspergillus flavus infection. The patient was managed with anticoagulation, antifungal therapy, and glycemic control. The left popliteal vein thrombus measured 3.5 cm, with thrombosis extending to the right superficial femoral vein. Blood glucose was 250 mg/dl, creatinine 1.5 mg/dl, and leukocyte count 18,000 cells/mm3. After treatment, leukocyte count normalized to 10.23×103 cells/mm3, and limb pain resolved. Follow-up revealed substantial clinical improvement by discharge on 11 January 2023. This case highlights the importance of early recognition and a multidisciplinary approach to managing infected pulmonary infarction and PCD in patients with DVT.